Surface‐Engineered Pt‐Ni(111) Nanocatalysts for Boosting Their ORR Performance via Thermal Treatment - Can Li; Xiaobo Chen; Jinfong Pan; Guangwen Zhou; Jiye Fang (ChemElectroChem)
Abstract The electrochemical oxygen reduction reaction (ORR) is critical for fuel cell application, and modifying surface structures of electrocatalysts has proven effective in improving their catalytic performances. In this study, we investigated surface‐engineered Pt−Ni nano‐octahedra subjected to annealing in various atmospheres. All octahedral nanocrystals retained their Pt−Ni {111} facets at an elevated temperature following the annealing treatments. Air annealing led to the formation of nickel‐rich shells on the Pt−Ni surface. In contrast, hydrogen (H₂) as a reducing gas facilitated the reduction of surface Ni species, incorporating them into the Pt−Ni bulk alloy, which resulted in superior mass activity and specific activity for ORR‐approximately 2.4 and 2.3 times as high as those from the unmodified counterpart, respectively. After 20,000 potential cycles, the H₂/Ar‐annealed Pt−Ni nano‐octahedra maintained a mass activity of 3.92 A/ mgPt , surpassing the initial mass activity of the unannealed counterparts (2.95 A/ mgPt ). These findings demonstrate a viable approach for tailoring catalyst surfaces to enhance performance in various energy storage and conversion applications.